A Metal-Free Approach for Brønsted Acid Promoted C–H Alkylation of Heteroarenes with Alkyl Peroxides - Zeng, Yuehua; Qian, Bo; Li, Yajun; Bao, Hongli (Synthesis, 2018)
A metal-free protocol for Minisci C–H alkylation of heteroarenes using alkyl peroxides as the alkylating reagents and internal oxidants simultaneously under promotion of Brønsted acid has been demonstrated. A series of alkyl substituted heteroarenes were readily prepared by the C–H alkylation in moderate to good yields. A possible pathway involving the addition of alkyl radical to heterocycle followed by rearomatization is described.
Keywords: metal-free conditions; Brønsted acid; C–H alkylation; heteroarenes; alkyl peroxides